2022
DOI: 10.3390/ijerph19031730
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic Increased Burnout and Bullying among Newly Graduated Nurses but Did Not Impact the Relationship between Burnout and Bullying and Self-Labelled Subjective Feeling of Being Bullied: A Cross-Sectional, Comparative Study

Abstract: (1) Background: The COVID-19 pandemic posed a great challenge to health care systems worldwide. Health care personnel, including nurses, work under high pressure and are overworked and overwhelmed, which results in a higher prevalence of burnout and workplace bullying, which further increases the intention to leave the nursing profession. (2) Methods: A comparative correlational and cross-sectional study design was adopted, and an online questionnaire was used to collect data between October 2019 and October 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…This result aligns with the previous research findings indicating that up to 40% of nurses annually experienced bullying in the workplace (Carter et al, 2013; Hutchinson et al, 2010; Quine, 2001; Sauer, 2018). This is an alarming rate, especially considering that exposure to workplace bullying is closely related to negative nurse outcomes such as work disengagement and burnout (Sauer, 2018; Serafin et al, 2022). According to the American Nurses Association (ANA) COVID‐19 impact assessment (2022), 66% of the nurses reported an increase in bullying at work during the pandemic and suggested that deteriorating work conditions during the pandemic were related to increased bullying (al Muharraq et al, 2022; Clegg, 1993; Huntington & Gilmour, 2001; Hutchinson et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This result aligns with the previous research findings indicating that up to 40% of nurses annually experienced bullying in the workplace (Carter et al, 2013; Hutchinson et al, 2010; Quine, 2001; Sauer, 2018). This is an alarming rate, especially considering that exposure to workplace bullying is closely related to negative nurse outcomes such as work disengagement and burnout (Sauer, 2018; Serafin et al, 2022). According to the American Nurses Association (ANA) COVID‐19 impact assessment (2022), 66% of the nurses reported an increase in bullying at work during the pandemic and suggested that deteriorating work conditions during the pandemic were related to increased bullying (al Muharraq et al, 2022; Clegg, 1993; Huntington & Gilmour, 2001; Hutchinson et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Historically, experienced RNs precepted and mentored NLRNs on the clinical units but as the number of expert nurses (i.e., >5 years' experience) decreased so did the breadth and depth of the support and expertise that was available for new nursing staff. 4,6 This change in staffing mix can negatively impact NLRNs' self-confidence and contribute their feeling anxious and overwhelmed, making it more important than ever to implement timely, effective, evidence-based strategies to enhance the well-being among NLRNs.…”
Section: Burnout and Newly Licensed Rns (Nlrns)mentioning
confidence: 99%
“…Although the prevalence of burnout rates vary by geographic location, specialty area, and method of measurement, it is estimated that up to 48% of nurses are experiencing some degree of burnout 5–7 . This is a concern because of the inverse relationship that exists between high clinician burnout and worse patient outcomes such as lower satisfaction, higher mortality, and increased hospital‐associated infection rates 8,9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A research study of 275 new nursing graduates found the prevalence of bullying and burnout is significantly higher among nurses who worked during the COVID-19 pandemic than among those who worked before the pandemic, but the pandemic has not impacted the level of the subjective assessment of bullying. 10 The researchers identified increased work stress as one of the main risk factors contributing to nurse bullying. Complaints were not limited to faculty-to-faculty incivility but also included top-down incivility.…”
mentioning
confidence: 99%